Response of chickpea genotypes (Cicer arietinum L.) to the fungi complex that causes wilt (Agro Productividad, 2024)
Objective: The objective of the present study was to evaluate the response of 10 chickpea genotypes from INIFAP to the damage caused by the fungal complex.Design/methodology/approach: Seedlings (15-day-old) of 10 genotypes (Blanco Sinaloa '92, Blanoro, Combo 743, CUGA2054, HOGA067, CUGA3168, CUGA08-1210, CUGA09-3160, R-12-1509 and R-12-1507) were inoculated by root immersion in a suspension of mycelial fragments of two isolates (high and low virulence) of each fungi: Fusarium languescens, M. phaseolina, S. rolfsii and S. sclerotiorum. Disease severity evaluation was performed 30 days after inoculation. The entire experiment was performed twice.Results: The genotypes showed greater susceptibility to S. sclerotiorum and S. rolfsii compared to F. languescens and M. phaseolina. The highly virulent isolates caused a significant difference in the severity of the disease in the genotypes evaluated.Findings/conclusions: All chickpea genotypes showed susceptibility to the fungal complex that causes wilt.